The responsibilities of platforms: a new constitutionalism to promote the legitimacy of decentralized governance - Suzor, Nicolas (AoIR Selected Papers of Internet Research, 2016)
This paper reviews the legitimacy terms of service of fifteen of the largest English-language social media platforms through the lens of the rule law. Each contract was analyzed to identify the extent to which they provided protections for due process interests of users. In all cases examined, the terms of service provided broad, unfettered discretion to platform owners. This is a serious failing from the perspective of the rule of law. Like constitutional documents, terms of service grant powers; but unlike constitutions, they rarely limit those powers or regulate the ways they are exercised. This paper takes stock of current debates about governance of the internet and the role of intermediaries in enforcing legal and social norms. I highlight the extents and limits of different forms of control that intermediaries can exercise over their users, and the social, legal, economic, and technical forces that act on intermediaries themselves. I argue that a new constitutionalism is needed to protect substantive and procedural rights in a decentralized regulatory environment. Recognizing that intermediaries always exercise some degree of regulatory control over their networks, I argue that some level of decentralization of governance is both inevitable and desirable. It will become increasingly important, however, to ensure that private platforms enforce rules in a manner that is regular, transparent, equally and proportionately applied, and fair. This paper seeks to progress this debate by providing a framework to evaluate the legitimacy of platform governance in practice.